Postpartum Changes in Uterine Position and Occurrence of Cesarean Scar Defects: A Retrospective Observational Study - Hongjie Pan; Ailing Gu; Yu Yang; Zhouhui Chen; Fengbing Liang (IMR Press, 2022)
Background: Over the past several decades, rates of cesarean delivery have increased considerably worldwide. As cesarean section (CS) may also result in changes to uterine position, the relationship between delivery modes, postpartum uterine position and cesarean scar defect (CSD) warrants elucidation. Materials & Methods: Here, we conducted a retrospective observational study evaluating 921 women (482 underwent vaginal delivery and 439 underwent CS) who had undergone transvaginal ultrasonography (TVU) early in their pregnancy (<8 weeks). Subsequent ultrasonography was performed 3-6 months postpartum to evaluate uterine position for all women and saline infusion sonohysterography (SIS) for women who underwent CS. The outcome was the uterine position for all of the women and the CSD for women underwent CS. Results: A total of 716 women (371 of whom underwent vaginal delivery and 345 of whom underwent CS) were concluded in the study. Postpartum uterine position was found to be significantly changed from anteflexion (81.9% for vaginal delivery and 82.0% for CS) to retroflexion (29.1% for vaginal delivery and 46.7% for CS) after both vaginal (p < 0.001) and CS (p < 0.001) deliveries. CSD was diagnosed by SIS in 146 of 345 (42.3 95% CI 37.1-47.6) women that underwent CS. CSD prevalence among anteflexed and retroflexed uterus were 46.7% (95% CI 39.5%-54.0%) and 37.3% (95% CI 29.7%-44.8%), respectively (p = 0.08). Conclusions: This study revealed that uterus became retroflexed in patients who underwent either CS or vaginal deliveries. CS resulted in a significantly greater proportion of retroflexed uterus than did vaginal delivery. CSD prevalence among women with retroflexed uterus in the postpartum has no difference with those with anteflexed uterus.